The peculiarities offish sex cycles and their ovary ripeness stages - N. I. Rabazanov; M. M. Shihshabekov; D. R. Aduyeva; G. Sh. Gadjimuradov; M. M. Nabiyev; D. M. Ramazanova (Юг России: экология, развитие, 2015)
All the ovogenesis and sex cycles peculiarities of the studied fishes are species-specific with biology particularity of different fishes including their reproductions. The research showed that the changes caused by different anthropogenic factors often change the whole process of gametogenesis thereby the character and fish reproduction intensity in the ecologically changed conditions.